RETÓRICA E OBSCENIDADE NO JORNALISMO GONZO: OS ECOS DE JAMES JOYCE EM FEAR AND LOATHING IN LAS VEGAS - Silva, Victor Fermino da (2021)
This work seeks to diagnose a dialectical element that goes beyond writing in the works Ulysses, by James Joyce, and Fear and Loathing in Las Vegas, by Hunter S. Thompson, using theater as a method of investigating language and eroticism as an arch-scripture linking the works in their echoes and comprising discursive production, both in experimental literature and in literary journalism, as a dialogical movement between the author and the world that houses it. Among the objectives of this research are the development of an idea of transgression as a dialectic, or as a phenomenological dialogue amid rhetoric, both in journalism and in literature. What dramatist rhetoric is and how it implies a Marxist reading method critical to the need for an end, but also how this verbal infinity represents a constant dialogue over time. And if the dialogue is constant, what is sought in this dissertation is the border and intentional point that produces the breaks in the currents of language to make it alive, and what we call transgression. Which transgression, if any, could be identified in which works? It is what this work seeks to answer or question even more with the chosen objects.